Sosialisasi Prosedur Perawatan Pembangkit Listrik Tenaga Mikrohidro Di Desa Ciasmara Kabupaten Bogor - Nur Abdi Insani; Rini Astuti; Edwar Muallim; Anto Cadmanto (CV. Multi Kreasi Media, 2026)
This activity is designed to provide a deep technical understanding to the people of Ciasmara Village regarding the routine maintenance of the Micro Hydro Power Plant, including cleaning the intake, inspecting the turbine, and maintaining the electrical system so that the plant can operate more reliably and efficiently. So that residents are able to handle daily maintenance and prevent damage that can interfere with operational continuity. This activity consists of several stages, including surveys, formulation of training manuals and modules, socialization and training, establishment of institutions and independent funding systems, and upstream environmental conservation education. The results of this activity are expected to make a real contribution to the development of a more targeted socialization strategy, increase community participation in technical maintenance, and support independent and sustainable plant management. In addition, this activity can also be considered for local governments, non-governmental organizations, and donor institutions in designing renewable energy-based community empowerment programs. With this activity, there will be a collective awareness from the community of the importance of maintaining and caring for the energy infrastructure that has been built, not only as a source of electricity, but also as a long-term socio-economic asset.